Study on Preparation of Oxygen Carrier Using Copper Slag as Precursor - Feng, Yan; Yang, Qianhui; Zuo, Zongliang; Luo, Siyi; Ren, Dongdong; Lin, Huan (Frontiers in Energy Research, 2021)
Copper slag, an important by-product of the copper smelting process, is mainly composed of 2FeO·SiO2, Fe3O4 and SiO2. Due to the sufficient metal oxides, copper slag is regard as a potential oxygen carrier (OC), which can be applied in chemical looping technology. This research proposed to use the granulated copper slag particles as precursor. Through this method, waste heat of the high-temperature slag can be fully recovered, eliminating the complicated copper slag pretreatment process. In this paper, the reactivity of granulated copper slag after redox calcination was studied by X-ray diffractometer (XRD) and the highest reactivity occurred at 1000℃. In addition, the oxygen release and absorption performance of OC were tested in thermal-gravimetric (TG). According to theoretical calculations, the mass loss caused by oxygen release accounts for 70.57% of the total loss and the mass reached 104.2% at 1000℃ in oxygen absorption experiment. The copper slag modified through calcining in redox condition was proved to be a promising oxygen carrier in chemical looping process. Furthermore, the performance research on OC also provided theoretical references for the operating paraments of OC circulating between air reactor and fuel reactor in practical chemical looping processes.